Kick, pass, and run. - Kessler, Leonard P., 1920- (New York, NY : Harper & Row Pub., Inc, 1965)
After observing a boy's football game, a group of animals organizes its own teams and game.
140
Accelerated Reader AR
Keywords: Football stories; Sports stories; Animals -- Fiction